Integrated Effects of Wheat Residue and Phosphorus Application on Rice Productivity and Soil Health under Salt Affected Soils: Effect of Crop Residue on Rice Production - Arshad Ullah, Muhammad; Ali, Arshad; Hyder, Syed Ishtiaq; Mahmood, Imdad Ali; Zaman, Badar-uz- (Biological Sciences - PJSIR, 2015)